2020
DOI: 10.1111/petr.13770
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of latent tuberculosis in hematopoietic stem cell transplant recipients: A First Report

Abstract: TB is an increasing health problem, and patients undergoing HSCT are more prone to develop tuberculosis. The aim of our study was to evaluate prevalence of latent tuberculosis in HSCT recipients. In this study, 84 patients (2 months to 18 years) who were candidates for HSCT at the referral hospital of Tehran Children's Medical Center were enrolled. The TST and the QFT‐GIT test were performed in all 84 patients, simultaneously. LTBI was considered when one of the tests was positive. Overall, the prevalence of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…[17] In their study conducted in Iran, Mahmoudi et al found that the prevalence of latent tuberculosis in HSCT recipients was 12%. [18]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] In their study conducted in Iran, Mahmoudi et al found that the prevalence of latent tuberculosis in HSCT recipients was 12%. [18]…”
Section: Discussionmentioning
confidence: 99%
“…[17] In their study conducted in Iran, Mahmoudi et al found that the prevalence of latent tuberculosis in HSCT recipients was 12%. [18] On chest X-ray, patients with fibrotic lung lesions suggestive of healed tuberculosis infection and a tuberculin skin test of ≥ 5 mm were considered test positive for the purified protein derivative tuberculin skin test. [19] Moreover, Bacillus Calmette-Guérin vaccine has been used to prevent tuberculosis infection in Turkey.…”
Section: Discussionmentioning
confidence: 99%